A potential role of reward and punishment in the facilitation of the emotion-cognition dichotomy in the Iowa Gambling Task - Singh, Varsha (Frontiers in Psychology, 2013)
The Iowa Gambling Task (IGT) is based on the assumption that a decision maker is equally motivated to seek reward and avoid punishment, and that decision making is governed solely by the intertemporal attribute (i.e., preference for an option that produces an immediate outcome instead of one that yields a delayed outcome is believed to reflect risky decision making and is considered a deficit). It was assumed in the present study that the emotion- and cognition-based processing dichotomy manifests in the IGT as reward and punishment frequency and the intertemporal attribute. It was further proposed that the delineation of emotion- and cognition-based processing is contingent upon reward and punishment as manifested in the frame of the task (variant type) and task motivation (instruction type). The effects of IGT variant type (reward vs. punishment) and instruction type (task motivation induced by instruction types: reward, punishment, reward and punishment, or no hint) on the intertemporal and frequency attributes of IGT decision-making were analyzed. Decision making in the reward variant was equally governed by both attributes, and significantly affected by instruction type, while decision making in the punishment variant was differentially affected by the two attributes and not significantly impacted by instruction type. These results suggest that reward and punishment manifested via task frame as well as the task motivation may facilitate the differentiation of emotion- and cognition-based processing in the IGT.